Analisis Perbedaan PSAK 22 dan IFRS 3 Tentang Kombinasi Bisnis Pada Penyusunan Laporan Keuangan Konsolidasi Pada Perusahaan di Indonesia - Afandi Afandi; Meira Chusnul Khotimah; Meylisa Eka Putri; Endang Kartini Panggiarti (Jurnal Akuntan Publik, 2025)
This research was conducted with the aim of knowing the differences between PSAK 22 and IFRS 3 regarding business combinations in the preparation of consolidated financial statements in companies in Indonesia. The type of method used is a qualitative method using a literature study approach because this approach provides an overview for researchers about the development of the topic of discussion. The data source used is secondary data that has been analyzed so that it can be developed to describe the research topic. Based on the results of the research analysis, there are several differences in PSAK 22 and IFRS 3, including the components of financial statements, disclosures in the statement of financial position, the term minority rights, extraordinary items, and in the presentation of long-term liabilities to be refinanced.